FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUNJUNGAN IBU HAMIL DALAM MELAKUKAN ANTENATAL CARE DI WILAYAH KERJA PUSKESMAS GLUMPANG BARO KABUPATEN PIDIE 2020 - Idawati Idawati; Yuliana Yuliana; Razali Razali (Jurnal Farmasindo, 2020)
Every year, around 1.5 million women experience pregnancy difficulties and more than half a million are accepted worldwide because of problems with pregnancy and childbirth. The purpose of this study was to study the Factors Associated with the Visit of Pregnant Women in Performing Antenatal Care. This study uses analytical research methods with Croossectional, with the technique of taking samples of 30 people. Univariate research results on obtaining respondents who visited antenatal care as many as 21 respondents (70.0%), respondents who have higher education are 19 respondents (63.3%), respondents who have sufficient income of 19 respondents (63.3%), respondents who received family support were 17 respondents (56.7%). The results of the bivariate study found that there was a significant relationship between education and antenatal care visits (P value = 0.008), there was a significant relationship between income and antenatal care visits (P Value = 0.001), there was a significant relationship between family support and antenatal care visits ( P value = 0.037). Conclusion there is a relationship of education with antenatal care visits, there is a relationship of income with antenatal care visits, there is a relationship of family support with antenatal care visits.